Exergoeconomic analysis and optimization of solar assisted hybrid cooling systems in full working conditions. (April 2022) - Zeng, Junquan; Li, Zeyu; Peng, Zeyu
Graphical abstract: Highlights: Full condition exergoeconomic optimization for solar cooling systems is proposed. Key component is optimized with tradeoff of cost and performance in whole process. Reduction rate of total cost rate in the near-optimal case is 16.5%. Difference of optimal sizes under different meteorological data is discussed. Abstract: Solar cooling technologies have considerable potential in reducing the energy consumption of buildings to realise carbon neutrality. However, they typically suffer during off-design operations due to variations in meteorological data and cooling demand. Hence, system optimization is extremely important to achieve the best thermo-economic performance considering all varying conditions. However, optimizations based on the two widely used approaches, i.e., annual simulation and exergoeconomics, can not fully resolve the aforementioned problems. Accordingly, the so-called full-condition exergoeconomic optimization is proposed and applied to a solar absorption-subcooled compression hybrid cooling system, which has potential for building cooling. First, a full-condition exergoeconomic model is formulated, and the impact of critical component size is subsequently analyzed. Finally, the size of key components is optimized based on the trade-off between capital investment and performance in all-working condition. Further, the variation among optimal sizes based on different meteorological data is compared. The total cost rate of the optimal case for the system utilized in Haikou is found to be 13.6% lower than that of the base case. The scales of the solar device and compression subsystem are found to be positively related to the local solar radiation intensity and cooling load. The study is anticipated to aid in rendering solar cooling facilities to be cost-effective in all-working condition.